Stable electrical, morphological and optical properties of titanium dioxide nanoparticles affected by annealing temperature - Nadzirah, Sh.; Uda, Hashim; Kashif, M.; Shahidah Arina, Shamsuddin (Springer Verlag, 2016)
Different TiO2 synthesization processes give different properties. Most of researches in material studies only focus on the morphological and optical properties of TiO2 while lacking in the effort of achieving stable electrical properties of the material. In engineering, stable electrical properties are vital in order to develop a device. Moreover, current technology needs more nanostructure application to enhance the performance of devices. In this paper, TiO2 nanoparticle was synthesized by sol–gel method using 1:0.1:9 ratios of titanium isopropoxide:acetic acid:ethanol, respectively. This synthesized TiO2 was able to respond in extremely small and consistent electrical reading (nanoampere). This metal oxide is good enough to be used as a material to develop ultra-high sensitive biosensor. Annealing process on the TiO2 film was able to improve its’ electrical conductivity. The three layers TiO2 coating were annealed at 400, 500, 600 and 700 °C and the surface morphologies, structural also electro-optical properties were studied using FESEM, XRD, UV–Vis and Keithley 6485 picoammeter. The XRD pattern shows the presence of stable anatase and rutile structures even at low temperature, whereas FESEM shows that annealingtemperature affects the particle size. The optical band gap of TiO2 thin films decreases from 3.74 to 3.34 eV as the annealing temperature increases. The current-to-voltage characteristics show that the conductivity decreases as the annealing temperature varies from 400to 700 °C. The output measurements indicated an improvement in electrical properties with annealing temperature.